An investigation on english speaking anxiety among efl vocational and technical high school students - EMİNOĞLU KÜÇÜKTEPE, SEVAL (My University, 2023)
The current study was carried out to determine which factors affect EFL vocational and technical high school students’ English-speaking anxiety and to make them self-evaluate their foreign language speaking anxiety, which affects their foreign language learning. For this purpose, vocational and technical high school students’ English-speaking anxiety and its relationship with the variables of gender, grade level, education level of parents and family income were investigated. To this end, the current study was designed in line with the general survey model. The population of the research consists of 387 students, who are in 9th, 10th, 11th and 12th grade levels at three vocational and technical Anatolian high schools in a city in the Marmara Region in the 2019- 2020 academic year. A \"Personal Information Form\" prepared by the researchers and the \"EFL Speaking Anxiety Scale\" prepared by Hortwitz, Hortwitz & Cope (1986) and adapted to Turkish by Öztürk (2012) were used as the data collection tools in the current study. The results of the study revealed that while vocational and technical high school students’ English-speaking anxiety did not vary significantly depending on their grade level, parents\" education level, family income, but varied significantly by gender. Accordingly, it was concluded that the female students studying at vocational and technical high schools have more English-speaking anxiety than the male students. Implications arising from these findings were also explained.
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Social Sciences and Humanities; Education; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities